The Spanish American War - Tuckett, Phil.; David, Keith; History Channel (Television network); NFL Films; Arts and Entertainment Network; New Video Group ([New York] : History Channel : A & E Television Networks : Distributed by New Video, 2007)
Over the course of 113 historic days in 1898, the United States established itself for the first time as a true international power, expanding American reach around the globe. The major battles of the war were fought simultaneously in Cuba and the Philippines, providing the might of a newly reorganized U.S. Navy. From the sinking of the USS Maine to the Battle of Manila Bay and the Rough Riders' legendary charge up San Juan Hill, some of the most iconic stories and images of the new American superpower were forged in this short war.
DVD, region 1; Dolby Digital stereo., subatomic digital.
Closed-captioned.
Originally broadcast on The History Channel in 2005.
Narrated by Keith David ; featuring Michael Cawelti.
Special features :"Theodore Roosevelt: Rough Rider to Rushmore" episode from A & E's Biography; history in the making featurette: "The Spanish-American War."
Keywords: Spanish-American War, 1898.; Spanish-American War, 1898.; San Juan Hill, Battle of, Cuba, 1898.; Manila Bay, Battle of, Philippines, 1898.; United States. -- Army. -- Volunteer Cavalry, 1st.; Historical television programs; Documentary television programs -- United States; Video recordings for hard of hearing people; Documentary -- Television special; War -- Television special